Microwave assisted synthesis of chalcogenide glasses - Prasad, Nupur (2010)
Chalcogenide glasses have several potential uses for new photonic devices for two reasons: i) their infrared (IR) transparency and ii) viscous flow at the glass transition temperature (Tg). Because of the latter, these glasses can be drawn to optical fibre and polished glass discs can be patterned above Tg for instance as planar waveguides. The fibre or waveguide shaped chalcogenide glasses have several potential uses as chemical sensors, biosensors, laser power delivery etc. and hence efforts have been made to synthesise high optical quality chalcogenide glasses. The well-established melt-quenching method was used as a comparative to prepare chalcogenide glass-melts in this project. Conventionally, the chalcogenide glass-melts are prepared using a rocking resistance furnace but this process is very long and cumbersome. To make the glass-melting process fast, simple and cost effective microwave heating was investigated instead in this project, and this was the main aim of the project. As2S3,Ge33As12Se55, Te20As30Se50 glasses were made with partial success and As2S3, Gel7As18Se65 glasses successfully, for the first time to the author's knowledge, through microwave heating in a domestic microwave oven (DMO) working at a frequency 2.45 GHz in less than an hour while the resistance heating method took about 1.5 days. The DMO output power was 800 W or 1000 W, and co-heating using both the microwaves and convection current heating to 220°C enabled some glass preparations to be carried out in ca. 10 minutes. The reactants were crushed manually for the DMO preparation of chalcogenide products keeping in mind that electric current tends to flow at the surface of the material which is known as 'skin effect'. The size of the silica glass melt-ampoule was kept as small as possible (normally - 10 cm) so that the DMO chalcogenide-melt could collect at the bottom of the ampoule and form a DMO chalcogenide rod product. The increased rate of reaction in the DMO compared to the rate of reaction in the rocking resistance furnace was attributed to the formation of plasma which caused a very high temperature (> 1000°C) of the reaction system leading to the almost instant melting of the some reactants. The boiling DMO chalcogenide-melt was seen in several cases but As/S = 2:3 (at%) did not boil when exposed to microwaves. Visually homogenous DMO chalcogenide-products were formed in each of the above stated compositions except in the case of DMO As-S product when four distinct layers could be seen. The red transparent portion of the DMO As-S sample was X-ray amorphous and showed no crystal feature in SAED (Selected area electron diffraction) using TEM (Transmission electron microscopy) whereas the non-glassy portion showed some crystalline peaks in XRD (X-ray diffraction) but showed no crystalline features in SAED. The DMO Ge/As/Se=33/12/55 (at%) rod product showed a single crystalline peak in the XRD pattern but it was completely amorphous according to SAED. On the other hand, the DMO Te/As/Se = 20/30/50 (at %) rod product showed slight evidence of crystallinity from SAED but was completely amorphous in XRD. DMO As/Se = 40/60 (at %) rod product and DMO Ge/As/Se= 17/18/65 (at %) rod did not show any crystalline structure from XRD and from SAED. The inhomogeneity of the DMO As-S glass was further reflected in the multiple Tgs observed using DTA (Differential thermal analysis) viz.:166°C, -194°C (broad) and 300°C in the first DTA run. Though, the sample showed a single Tg value of 202°C during the second DTA run after quenching in-situ the sample from the first DTA run. The stoichiometry of this glass wasAs43.9Se56.1 when observed through EDX (Energy dispersive X-ray analysis) which was performed using ESEM (Environmental scanning electron microscopy) showing that the glass was inhomogeneous. The DMO As/Se = 2:3 (at %) rod product showed a single Tg value of 180°C ± 5°C and the stoichiometry was found to be As40.1Se59.9 from EDX analysis which was very close to the desired value. The DMO rod product obtained from the composition Ge/As/Se = 17/18/65 showed a single Tg value of 246°C ± 5°C and the observed stoichiometry of the DMO chalcogenide product was Gel7.6As19.2Se63.5. Whereas the Ge32.8As11.0Se56.4 DMO rod product could be made from the batch composition Ge/As/Se=33/12/55 with a Tg value of 368°C ± 5°C but the conventionally prepared glass exhibited a stoichiometry Ge33.8As12.5Se50.6 with Tg value 371 DC± 5°C showing that a slight increase in percentage of germanium in the glass composition increases the Tg value. The Te19.6As30.4Se50.0 DMO rod product was obtained from Te/As/Se = 30/20/50 batch composition having a Tg value of 371°C ± 5°C showing that the experimental values for the stoichiometry and Tg of the product were very close to the desired value. A sample of Te/As/Se = 20/30/50 was heated in the DMO only for 5 minutes when stoichiometry of the product was found to be Te19.6As32.6Se47.8 showing that prolonged exposure of microwaves, which facilitated boiling, was important for homogenisation of the product (note that DMO As-S product never boiled) since the ampoule was not rocked inside the DMO. It was observed that optical absorption at 2.9 urn wavelengths due to hydroxide contamination for the DMO As-S product was reduced to - 3% of that of the AS2S3 glass made through conventional heating. The absorption bands for -OH group at 2.9 urn and H20 at 6.3 mum were very low in almost all the DMO products. Some carbon and silica contamination was found to be slightly larger in DMO products than that present in the conventionally prepared products and the reasons for this are not known at present. The DMO chalcogenide products were obtained reproducibly except in the cases of the DMO As-S product.